Prediction of Parenting Styles Based on Childhood Trauma and Early Maladaptive Schemas in Married University Students - Izadi, Elham; Khakpour, Reza (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The aim of the present study was to predict parenting styles based on childhood trauma and early maladaptive schemas in married university students. This study was conducted to contribute to the promotion of healthy parent–child relationships and to improve the overall well-being of married students and their children.Methods and Materials: In terms of purpose, this research was applied, and in terms of method, it was a descriptive–correlational study with a predictive approach. The statistical population consisted of all married students of the Islamic Azad University, Roudehen Branch in the second semester of the 2023–2024 academic year (approximately 1500 individuals), from whom 270 participants were selected through convenience and voluntary sampling. The research instruments included the Baumrind Parenting Styles Questionnaire, the Childhood Trauma Questionnaire (CTQ), and the Young Early Maladaptive Schemas Questionnaire (Short Form). Data were analyzed using descriptive statistics and simple linear regression analysis in SPSS version 25.Findings: In the analysis of 270 married students, correlational results indicated that childhood trauma had a negative relationship with permissive parenting style (r = −0.44, p < 0.01) and authoritative parenting style (r = −0.33, p < 0.01), and a strong positive relationship with authoritarian parenting style (r = 0.77, p < 0.01). Furthermore, most domains of early maladaptive schemas showed significant relationships with parenting styles, including disconnection and rejection (r = −0.47 to −0.61) and over-vigilance/inhibition (r = −0.62 to 0.66). Linear regression results also showed that childhood trauma predicted only authoritative parenting style (β = −0.20, p < 0.01) and authoritarian parenting style (β = 0.536, p < 0.001). Among schema domains, disconnection and rejection (β = −0.36, p < 0.001) and over-vigilance/inhibition (β = −0.49, p < 0.001) predicted permissive parenting style. Additionally, four main domains—disconnection and rejection, impaired autonomy and performance, impaired limits, and over-vigilance/inhibition—predicted a decrease in authoritative parenting style (β = −0.23 to −0.44). Moreover, impaired autonomy and performance (β = 0.18), impaired limits (β = 0.53), other-directedness (β = 0.15), and over-vigilance/inhibition (β = 0.25) predicted an increase in authoritarian parenting style. The largest effect size was related to the role of impaired limits in predicting authoritarian parenting style (η² = 0.28).Conclusion: The findings of the study indicate that adverse childhood experiences and the development of early maladaptive schemas can play a significant role in shaping parenting patterns in adulthood. Paying attention to these factors in educational programs and psychological interventions can contribute to improving parenting styles, enhancing parent–child relationships, and increasing the psychological well-being of families.